The Effect Of Growth Opportunities, Company Size And Profitability On Accounting Conservatism In Lq45 Companies For The Period 2019-2021 - Ayu Puji Hastuti; Hetty Muniroh (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This research aims to ascertain how the result of growth opportunities, company size and profitability on accounting conservatism. The object of this study is companies included in the LQ45 index for the years 2019 to 2021The information used in this study comes from the financial statements listed for the 2019–2021 period on the Indonesia Stock Exchange. The number of LQ45 companies sampled was 13 companies with a three-year observation period. The total sample of this study with the purposive sampling research method was 39. The dependent variable in this study is accounting conservatism, while the independent variables are growth opportunities, company size and profitability. In this work, multiple linear regression analysis is used for hypothesis testing. The findings of this research are growth opportunities have a significant negative effect on accounting conservatism, company size has a negative and insignificant effect on accounting conservatism and profitability has a positive and insignificant effect on accounting conservatism.